CD8+T cell-derived CD40L mediates noncanonical cytotoxicity in CD40-expressing cancer cells - Schiele, Phillip; Japp, Alberto Sada; Stark, Regina; Sattelberg, Joanna J.; Nikolaou, Christos; Kornhuber, Gereon; Abbasi, Parya; Ding, Nina; Rosnev, Stanislav; Meinke, Stefan; Mühle, Kerstin; Loyal, Lucie; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
T cells and their effector functions, in particular the canonical cytotoxicity of CD8+T cells involving perforin, granzymes, Fas ligand (FasL), and tumor necrosis factor related apoptosis inducing ligand (TRAIL), are crucial for tumor immunity. Here, we reveal a previously unidentified mechanism by which CD40L-expressing CD8+T cells induce cytotoxicity in cancer cells. In murine models, up to 50% of tumor-specific CD8+T cells expressed CD40L, and conditional CD40L ablation in CD8+T cells alone led to tumor formation. Mechanistically, CD40L+CD8+ T cells can induce cell death in CD40-expressing cancer cells by triggering caspase-8 activation. We demonstrate that a gene signature for resistance to CD40 signaling-induced cell death strongly correlates with worse survival in different human cancer cohorts. Our results introduce CD40L as a rather counterintuitive, noncanonical cytotoxic factor that complements the capabilities of CD8+T cells to combat cancers and has the potential to enhance the efficacy of immunotherapies.